A triclinic polymorph of bis(μ-di-tert-butylphosphanido)bis[(di-tert-butylphosphane)palladium(I)] - Jens Breunig; Hans-Wolfram Lerner; Michael Bolte (Acta Crystallographica Section E, 2012)
A new polymorph of the title compound, [Pd2(C8H18P)2(C8H19P)2], has been found. It belongs to the triclinic P-1 space group, whereas the known form [Leoni, Sommovigo, Pasquali, Sabatino & Braga (1992), J. Organomet. Chem. 423, 263–270] crystallizes in the monoclinic C2/c space group. The title compound features a dinuclear palladium complex with a planar central Pd2(μ-P)2 core (r.m.s. deviation = 0.003 Å). The Pd—Pd distance of 2.5988 (5) Å is within the range of a PdI—PdI bond. The molecules of both polymorphs are located on a crystallographic centre of inversion. The molecular conformations of the two polymorphs are essentially identical. The crystal packing patterns, on the other hand, are slightly different.